Pelaksanaan Pembelajaran Matematika Secara Daring di SMP Negeri 11 Mataram Selama Masa Pandemi Covid-19 Tahun Pelajaran 2021/2022 - Nur Idamayanti; Muhammad Turmuzi; Wahidaturrahmi Wahidaturrahmi; Baidowi Baidowi (Griya Journal of Mathematics Education and Application, 2022)
This research aims to describe the implementation of mathematics learning online and describe the strategies used by teachers in mathematics learning during the Covid-19 pandemic at SMPN 11 Mataram. This type of research is qualitative research. All students and teachers of mathematics learning at SMPN 11 Mataram are population, where the sample number of 3 mathematics teachers and 76 students are selected by random sampling cluster rules. Data collection uses questionnaires to obtain data on the implementation of mathematics learning online while the interview profit is to explore more in-depth information about teacher strategies in online mathematics learning. From this study, the results were obtained that: (1) The implementation of online mathematics learning in general at SMPN 11 Mataram is in the category quite well. Mathematics learning carried out online is at their respective homes, students use whatsapp, google meet and google forms. (2) Assessment of learning processes and outcomes, evaluation and supervision of the learning process is in the category of good enough where the teacher provides written test analysis and corrects and returns student assignments. Supervision of the online learning process is carried out by teachers by controlling students from the beginning of the lesson to the end of the lesson while parents provide supervision at home by reminding their children to complete assignments from school.